Biocompatibility and antioxidant activity of a novel carrageenan based injectable hydrogel scaffold incorporated with Cissus quadrangularis: an in vitro study - Sruthi Sairaman; M. S. Nivedhitha; Deepti Shrivastava; Meshal Aber Al Onazi; Hmoud Ali Algarni; Mohammed Mustafa; Ali Robaian Alqahtani; Nouf AlQahtani; Kavalipurapu Venkata Teja; Krishnamachari Janani; Rajalakshmanan Eswaramoorthy; M. P. Sudhakar; et al. (BMC, 2022)
Abstract Background Over the past years, polysaccharide-based scaffolds have emerged as the most promising material for tissue engineering. In the present study, carrageenan, an injectable scaffold has been used owing to its advantage and superior property. Cissus quadrangularis, a natural agent was incorporated into the carrageenan scaffold. Therefore, the present study aimed to assess the antioxidant activity and biocompatibility of this novel material. Methods The present in vitro study comprised of four study groups each constituting a sample of 15 with a total sample size of sixty (n = 60). The carrageenan hydrogel devoid of Cissus quadrangularis acted as the control group (Group-I). Based on the concentration of aqueous extract of Cissus quadrangularis (10% w/v, 20% w/v and 30% w/v) in carrageenan hydrogel, respective study groups namely II, III and IV were considered. Antioxidant activity was assessed using a 1,1-diphenyl-2-picrylhydrazyl radical scavenging assay, whereas the biocompatibility test was performed using a brine shrimp lethality assay. The microstructure and surface morphology of the hydrogel samples containing different concentrations of Cissus quadrangularis aqueous extract was investigated using SEM. One-way ANOVA with the post hoc tukey test was performed using SPSS software v22. Results A significant difference (P < 0.05) in the antioxidant activity was observed among the study groups. Group III reported the highest activity, whereas the control group showed the least antioxidant activity. Additionally, a significant (P < 0.01) drop in the antioxidant activity was observed in group IV when compared with group III. While assessing the biocompatibility, a significant (P < 0.001) dose-dependent increase in biocompatibility was observed with the increasing concentration of aqueous extract of Cissus quadrangularis. SEM analysis in group III showed even distribution throughout the hydrogel although the particles are close and densely arranged. Reduced antioxidant activity in group IV was probably due to clumping of the particles, thus reducing the active surface area. Conclusion Keeping the limitations of in vitro study, it can be assumed that a carrageenan based injectable hydrogel scaffold incorporated with 20% w/v Cissus quadrangularis can provide a favourable micro-environment as it is biocompatible and possess better antioxidant property.